Design of Electronically Controllable Multifunction Active Filter with Amplitude Controllability Using Two Commercially Available ICs - Narumol Onanong; Piya Supavarasuwat; Daungkamol Angamnuaysiri; Surapong Siripongdee; Amornchai Chaichana; Winai Jaikla; Peerawut Suwanjan (Journal of Electrical and Computer Engineering, 2022)
In this contribution, the design and analysis of an active multifunction biquad filter that provides five voltage-mode filtering configurations in the same core filtering circuit are presented. The design emphasizes using the commercially available ICs, LT1228, which are easy for off-the-shelf implementation and cheaper compared with the chip implementation. The proposed multifunction filter is realized from two commercial LT1228 ICs as the active function block, combined with five passive elements (three resistors and two capacitors) with three input voltage nodes and a single output voltage node. The following advantages are given for this design: (i) it provides high-pass (HP), low-pass (LP), band-stop (BS), band-pass (BP), and all-pass (AP) filtering functions; (ii) orthogonal and electronic tuning of the natural frequency ω0 and bandwidth (the quality factor: Q); (iii) output voltage node of the proposed circuit is low impedance; (iv) passband voltage gain is controllable; and (v) matching condition and extra double gain voltage-mode amplifier are not required. The effect of the parasitic element in LT1228 on the filter performance is analyzed and included to strengthen the design idea. The PSpice simulation results using LT1228 with ±5 V and the experimental results tested from the hardware implementation are given to prove the validity of the designed multifunction filter.